Hepatocellular carcinoma risk in chronic hepatitis B virus–infected compensated cirrhosis patients with low viral load. Issue 3 (3rd July 2015) - Sinn, Dong Hyun; Lee, Junggyu; Goo, Juna; Kim, Kyunga; Gwak, Geum‐Youn; Paik, Yong‐Han; Choi, Moon Seok; Lee, Joon Hyeok; Koh, Kwang Cheol; Yoo, Byung Chul; Paik, Seung Woon
<x xml:space="preserve">Abstract</x> Controversy exists about whether antiviral therapy (AVT) should be recommended for compensated cirrhosis patients with chronic hepatitis B virus (HBV) infection and detectable, but low, serum HBV‐DNA levels. A retrospective cohort of 385 treatment‐naïve, HBV‐related compensated cirrhosis patients (mean age: 51.1 ± 9.7 years; 66% male) with low HBV‐DNA levels (<2, 000 IU/mL) was assessed for the development of hepatocellular carcinoma (HCC). During a median of 5.6 years of follow‐up, HCC had developed in 37 (9.6%) patients. The 5‐year cumulative HCC incidence rate was 2.2%, 8.0%, and 14.0% for patients with undetectable HBV DNA (<12 IU/mL), low HBV‐DNA levels plus normal alanine aminotransferase (ALT) levels, and low HBV‐DNA levels plus elevated ALT levels at baseline (P = 0.011). During follow‐up, 71 patients maintained undetectable HBV‐DNA levels, and 126 experienced HBV‐DNA elevation over 2, 000 IU/mL. AVT was initiated in 77 patients. In patients without AVT, the 5‐year cumulative HCC incidence rates were 13.3%, 8.8%, and 1.4% for those who experienced HBV‐DNA elevation, those who maintained detectable, but low, HBV‐DNA levels, and those who maintained undetectable HBV‐DNA levels, respectively. The 5‐year cumulative HCC incidence rate was 5.9% for patients who started AVT; longer AVT duration and longer complete virological response (<12 IU/mL) duration was associated with lower HCC risk. Conclusion: Compensated cirrhosis patients with detectable, but low, viral load were not at low risk for HCC, and AVT was associated with lower HCC risk, suggesting that prompt AVT should be considered for these patients. (Hepatology 2015;62:694–701)